Scaling Up Youth-Focused Interventions in the Multi-Country HIV/AIDS Programs and Building Capacity of Civil Society Organizations, Case from Zambia : An Assessment Report - World Bank (World Bank, Lusaka, 2013)
Zambia is among countries with high HIV/AIDS prevalence, 16 percent among adult population aged 15 to 49 years. Prevalence among urban population is twice that of rural dwellers, 23 percent for urban and 11 percent for rural residents. Like other African countries, youth and women are the groups highly infected and affected by HIV/AIDS. As part of the scaling up effort, the World Bank (WB) commissioned a local consultant to undertake this exercise, focusing mainly on the capacity building needs of youth-serving organizations, civil society organizations, including youth organizations, sectoral ministries working on youth-focused HIV/AIDS initiatives. In this exercise young people and youth organizations were targeted as key sources of information. Specifically, the objectives of the assessment are: a) assess the current state of programming for youth-focused HIV activities in the country; b) determine the level of funding for youth-focused activities and effectiveness of youth-focused activities within the Multi-Country HIV/AIDS Programs (MAP) and other major HIV programs; c) identify factors that may foster or hinder attention to youth in the MAP and other HIV interventions; d) define priority capacity building needs among Civil Society Organizations (CSOs) working mainly on youth-focused HIV/AIDS interventions; and e) identify potential implementing partners who will carry out capacity building activities. There is increasing recognition of the devastating effects of HIV/AIDS among youths and for this reason, there is growing consensus that youths must be made key players and equal participants in the fight against the pandemic. National policies and programmes are now paying attention to and recognising the critical role of youths in the national response to the HIV/AIDS situation.